2019
DOI: 10.1177/1468087419872113
|View full text |Cite
|
Sign up to set email alerts
|

Lubrication analysis for the piston ring of a two-stroke marine diesel engine taking account of the oil supply

Abstract: The piston ring is one of the most important parts of a two-stroke marine diesel engine. It is lubricated by a special mode in which the lubricating oil is directly injected into the liner’s inner surface. In this article, taking account of the oil supply, a piston ring lubrication model is developed based on oil mass conservation. The lubrication region of this piston ring–cylinder liner is divided into inlet, core lubrication, and outlet regions, with the oil supply being converted into an oil film. The impa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 26 publications
0
25
0
Order By: Relevance
“…Unfortunately, models of lubrication in marine applications are more challenging to verify than those for automotive systems due to the operating cost and scale of marine engines. Tests have been conducted in bench test apparatus [11] and engine scale laboratory test equipment [12], but they do not fully replicate the true conditions of operating engines. However, some limited data is available.…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, models of lubrication in marine applications are more challenging to verify than those for automotive systems due to the operating cost and scale of marine engines. Tests have been conducted in bench test apparatus [11] and engine scale laboratory test equipment [12], but they do not fully replicate the true conditions of operating engines. However, some limited data is available.…”
Section: Introductionmentioning
confidence: 99%
“…The piston ring–cylinder liner (PRCL) conformation is a critical aspect for friction within the piston–liner section of the engine. 5,6 On one hand, limited ability of the piston rings to conform to the bore shape will lead to oil consumption and corresponding emission of particulate and hydrocarbons. On the other hand, higher piston ring tension, which is required to achieve the oil consumption and exhaust emission requirements, leads to increased friction losses and ultimately results in increased fuel consumption and GHG emissions.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the fully flooded condition is assumed in the current study. The research on the deformation and starved lubrication can be found in Okamoto, 38 Liu et al, 39 Li et al, 40 Syed and Wani. 41…”
Section: Calculationmentioning
confidence: 99%